Macrophage polarization phenotype regulates adiponectin receptor expression and adiponectin anti‐inflammatory response. Issue 2 (12th November 2014) - van Stijn, Caroline M. W.; Kim, Jason; Lusis, Aidons J.; Barish, Grant D.; Tangirala, Rajendra K.
ABSTRACT: Adiponectin (APN), a pleiotropic adipokine that exerts anti‐inflammatory, antidiabetic, and antiatherogenic effects through its receptors (AdipoRs), AdipoR1 and AdipoR2, is an important therapeutic target. Factors regulating AdipoR expression in monocyte/macrophages are poorly understood, and the significance of polarized macrophage activation in controlling AdipoR expression and the APN‐mediated inflammatory response has not been investigated. The aim of this study was to investigate whether the macrophage polarization phenotype controls the AdipoR expression and APN‐mediated inflammatory response. With the use of mouse bone marrow and peritoneal macrophages, we demonstrate that classical activation (M1) of macrophages suppressed (40‐60% of control) AdipoR expression, whereas alternative activation (M2) preserved it Remarkably, the macrophage polarization phenotypes produced contrasting inflammatory responses to APN (EC50 5 μg/ml). In M1 macrophages, APN induced proinflammatory cytokines, TNF‐α, IL‐6, and IL‐12 (>10‐fold of control) and AdipoR levels. In contrast, in M2 macrophages, APN induced the anti‐inflammatory cytokine IL‐10 without altering AdipoR expression. Furthermore, M1 macrophages adapt to a cytokine environment by reversing AdipoR expression. APN induced AdipoR mRNA and protein expression by up‐regulating liver X receptor‐α (LXRα) in macrophages. These results provide the first evidence that macrophage polarization is a key determinant regulating AdipoR expression and differential APN‐mediated macrophage inflammatory responses, which can profoundly influence their pathogenic role in inflammatory and metabolic disorders.—van Stijn, C. M. W., Kim, J., Lusis, A. J., Barish, G. D., Tangirala, R. K. Macrophage polarization phenotype regulates adiponectin receptor expression and adiponectin anti‐inflammatory response. FASEB J . 29, 636‐649 (2015). www.fasebj.org